Lawrence Welcomes Authors for Fox Cities Book Festival - Lawrence University (Lux, 2013)
Lawrence University will host visits by three authors and a documentary film screening in conjunction with the 6th annual Fox Cities Book Festival. All events are free and open to the public. Lawrence is one of the sponsors of the book festival. Writer and neuroscientist Lisa Genova, author of the New York Times’ bestsellers “Love Anthony,” “Still Alice” and “Left Neglected” speaks Friday, April 19 at 6:30 p.m. in Harper Hall. Genova, who writes “about people living with neurological diseases and conditions that are feared, ignored, or misunderstood,” has appeared on Dr. Oz and CNN and was featured in the Emmy Award-winning documentary film about Alzheimer’s, “To Not Fade Away.” Humorist Michael Perry, author of the memoirs “Population 485: Meeting Your Neighbors One Siren at a Time,” “Truck: A Love Story” and “Coop: A Year of Poultry, Pigs and Parenting,” appears Saturday, April 20 at 12 noon in the Warch Campus Center. Perry, who grew up on a small dairy farm and today makes his home in rural Wisconsin, has written for The New York Times Magazine as well as Esquire, Outside and Backpacker magazines and is a contributing editor to Men’s Health. Award-winning Canadian food journalist Jennifer Cockrall-King discusses her book “Food and the City: Urban Agriculture and the New Food Revolution” Monday, April 22 at 7 p.m. in Thomas Steitz Hall of Science Room 102. Cockrall-King examines alternative food systems in cities around the globe that are shortening their food chains, growing food within their city limits and taking their “food security” into their own hands Monday, April 22 at 7 p.m. in Thomas Steitz Hall of Science Room 102. Her appearance is supported by Lawrence’s Spoerl Lecture in Science and Society. The film “Chasing Ice,” a documentary by National Geographic photographer James Balog will be shown Tuesday, April 16 at 7 p.m. in the Warch Campus Center cinema. The film follows Balog’s journey across the Arctic documenting melting glaciers over a three-year period. A discussion will be held following the ...